Sistem Informasi Pengajuan Cuti dan Pengelolaan Surat Berbasis Web pada PT. XYZ - Fitriana Silvia (mijournal.org, 2026)
PT. XYZ is a company engaged in logistics and transshipment services. In its administrative activities, leave application processes and the management of incoming and outgoing correspondence are still handled manually, resulting in longer approval times, difficulties in document retrieval, and a higher risk of data loss. This study aims to develop a web-based leave application and correspondence management information system for PT. XYZ to improve the effectiveness and efficiency of administrative processes. The system was developed using the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance stages. PHP was used as the programming language and MySQL as the database management system. System testing was conducted using the Black Box Testing method to ensure that all system functions operated according to user requirements. The results indicate that the system successfully integrates leave applications, incoming and outgoing mail management, and document archiving into a single application. Based on the testing results, all system functions operated properly and met user requirements. The developed system can accelerate administrative processes, facilitate data retrieval, and improve the effectiveness of document management within the company.